Analisis Resiko pada Operasional Konveksi PT. Alam Pelangi Jaya Memakai Metode House of Risk - Rahman, Achmad Khabibbur; Nuruddin, Mochammad; Hidayat, Hidayat (LPPM Universitas Pahlawan Tuanku Tambusai, 2023)
Operational risk is the non-functioning of a system, human resources, technology, etc. which causes deviations due to non-conformity from what is expected. Many factors cause operational risks to occur. In this research, a case study of convection operational risks, there are risks that cause financial losses to the company. By analyzing risks, risk-causing factors, and mitigation techniques, the House of Risk method is used in this study to identify hazards in convection operations. There are 12 risk agents with 20 identified causes, resulting in 12 priority strategies, namely looking for closer suppliers, holding meetings with company operations/coordinating using language/actions that are easy to understand, creating appropriate K3 SOP, maintaining every tool used, placing orders. via telephone, carrying out selection with experts for each worker, assessing the reasons behind delays and putting new plans in place to schedule the delivery of goods, enforcing severe rules against those who break them, getting the company's diesel engines ready, creating a list of design drawings that have been submitted and those that haven't, Creating and altering design creation processes